Clinical feature and Genetics in Rett syndrome; A report on Iranian patients - Karimzadeh, Parvaneh; Kheirollahi, Majid; Houshmand, Seyed Massoud; Dadgar, Sepideh; Aryani, Omid; Yaghini, Omid (Iranian Journal of Child Neurology, 2019)
Background: Rett Syndrome is characterized by normal development for the first 6–18 months of life followed by the loss of fine and gross motor skills and the ability to engage in social interaction. Mutations methyl CpG-binding protein 2 gene (MECP2) have been found in the majority of patients. This study was performed to investigate the relation of Rett clinical diagnosis and its relation with mutations in MECP2. Materials and Methods: children suspected to Rett syndrome were invited to take part in this study. Those who had met classic Rett syndrome diagnostic criteria were enrolled. Severity of symptoms was assessed for all patients. Of peripheral blood samples collected in EDTA tubes, the genomic DNA was extracted by standard salting out method. MEPC2 gene mutation was studied by DNA sequencing method. Results and conclusion: 23 patients accepted to participate in the study. 11(47.8%) patients had MECP2 gene mutation meanwhile 12 ones (52.2%) had no mutation. change in genetics was in association with phenotypical manifestations. The most prevalent mutation was p.v288 which is mostly in association with partially or uncontrolled seizures. This was the first time that Rett syndrome patients were studied in both clinical manifestations and genetic changes in Iran.